Trending Up: A Cross-Cohort Exploration of STEM Career and Technical Education Participation by Low-Income Students. Issue 1 (2nd January 2020) - Plasman, Jay Stratte; Gottfried, Michael A.; Klasik, Daniel
Abstract: The ink from the reauthorization of the Perkins Act – the federal policy governing career and technical education (CTE) – in the summer of 2018 is still fresh. This much-needed update builds upon some of the major tenets of the 2006 version, including emphases on increasing the participation of low-income students in CTE and encouraging CTE coursework that focuses on building math and science skills while also providing technical skills for participation in high-skill, high-demand careers. Using two nationally representative datasets, in between which the 2006 Perkins Act was reauthorized, we explore whether there were any observable differences in participation in these math and science based CTE courses by low-income students over time. Implications are discussed.